Angina-like chest pain: a joint medical and psychiatric investigation. Issue 756 (October 1988) - Colgan, S. M.; Schofield, P. M.; Whorwell, P. J.; Bennett, D. H.; Brooks, N. H.; Jones, P. E.
Abstract : Sixty three patients with chest pain typical of angina and who had normal coronary angiograms were investigated for left ventricular, oesophageal and psychiatric abnormalities. An additional 21 patients, age and sex matched, who had angina and significant coronary artery disease were also studied. Eighty six per cent of the 63 patients without evidence of coronary artery disease could be demonstrated to have a physical abnormality (left ventricular dysfunction in 35%, oesophageal disorder 51%). There was, however, a wide variation in the incidence of psychiatric morbidity between the diagnostic subgroups-18% in left ventricular dysfunction, 29% in those with coronary artery disease and 59% in patients with oesophageal disorders (P less than 0.01). Thus failure to identify left ventricular dysfunction and inclusion of such subjects in psychological assessments of 'angiogram-negative' chest pain might give misleading results. This study confirms that patients with angina and normal coronary angiography have a high incidence of oesophageal disorders. However psychiatric illness is also common in this group of subjects and management needs to take both these factors into account.